2013
DOI: 10.1242/jeb.087296
|View full text |Cite
|
Sign up to set email alerts
|

Landmarks and ant search strategies after interrupted tandem runs

Abstract: During a tandem run, a single leading ant recruits a single follower to an important resource such as a new nest. To examine this process, we used a motorized gantry, which has not previously been used in ant studies, to track tandem running ants accurately in a large arena and we compared their performance in the presence of different types of landmark. We interrupted tandem runs by taking away the leader and moved a large distant landmark behind the new nest just at the time of this separation. Our aim was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…2A, last row). While it is tempting to discuss this in the context of laterality, for which there is evidence in ants and bees at both the population and individual level (Basari et al, 2014;Frasnelli et al, 2012;Hunt et al, 2014;Ong et al, 2017), we think that is not the case here. We think the bias may be Table S1).…”
Section: Discussionmentioning
confidence: 84%
“…2A, last row). While it is tempting to discuss this in the context of laterality, for which there is evidence in ants and bees at both the population and individual level (Basari et al, 2014;Frasnelli et al, 2012;Hunt et al, 2014;Ong et al, 2017), we think that is not the case here. We think the bias may be Table S1).…”
Section: Discussionmentioning
confidence: 84%
“…Would these ants in their natural habitat even have the opportunity to visit more than one nest, and therefore be in a position to make comparisons? There have been no field studies that address this directly, however, inter-nest distances in the wild can be low (frequently less than 30 cm; E. J. H. Robinson and N. R. Franks 1992–2013, personal observation) compared with the much greater distances over which laboratory colonies will readily emigrate, with scouts visiting pairs of nests that are separated by as much as 1.2 m [20,37]. This gives an indication that we would expect some ants to have the opportunity to encounter multiple sites in the wild, however, across the scouting population, the information obtained may be very variable.…”
Section: Discussionmentioning
confidence: 99%
“…Population-level asymmetry has also been observed in the red wood ant Formica aquilonia , where ants receiving food via trophallaxis use the right antenna to stimulate their donor ant significantly more than the left antenna [ 8 ]. Recent research has found that workers of the house-hunting ant Temnothorax albipennis seem to rely more on their right eye to recognize landmarks for navigation [ 9 ]. This is similar to the finding that bees ( Apis mellifera ) predominantly use their right eye for learning and/or detecting objects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%